Virus Quantification Methods with Focus on Marek's Disease Viruses - Piriaei, Mohammad Reza; Razmyar , Jamshid; Dolatyabi , Sara; Bozorgmehrifard, Mohammad Hasan (Journal of Poultry Sciences and Avian Diseases, 2023)
Marek's disease (MD) is a significant concern in the poultry industry, causing neoplastic disease and substantial economic losses. MDV-1, MDV-2, and MDV-3 are the three serotypes of the herpesvirus that cause MD, each with unique traits and interactions with the host. Vaccination is the primary preventive measure, but some vaccinated flocks still experience losses, often due to suboptimal vaccine dosages. Accurate quantification of the virus is crucial for understanding its dynamics, evaluating vaccine efficacy, and ensuring the health and productivity of poultry populations. Virus quantification methods fall into two main categories: infectivity assays and chemical/physical assays. Infectivity assays detect active, infectious virions, such as plaque, focus formation, and endpoint dilution. Chemical/physical assays, including the hemagglutination assay, transmission electron microscopy, flow cytometry, and qPCR, target specific components of the virion. However, these methods cannot distinguish between infectious and inactivated virions, potentially leading to overestimating viable viral populations. Marek's disease viruses (MDVs) can be quantified using in vitro plaque assays in susceptible cell cultures. The viral plaque assay determines the number of plaque-forming units (pfu) in a virus sample. Titration procedures for vaccine strains are similar to those for pathogenic variants. It is crucial to assess the dose of reconstituted MD vaccine (in PFU per chicken) to identify potential vaccine inefficacies and prevent outbreaks in the field. Accurate virus quantification is pivotal in understanding viral kinetics, optimizing therapeutic interventions, evaluating vaccine effectiveness, and preventing Marek's disease outbreaks in poultry.